1975
DOI: 10.1093/jnci/54.6.1373
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Microspectrophotometric Studies on Spontaneous Melanomas in Xiphophorus helleri

Abstract: Melanomas developed in both sexes of a strain of Tuxedo variety of the swordtail (Xiphophorus helleri) at a relative frequency of 10-15%. They did not metastasize. However, the tumor margin had infiltratitive growth and subsequently ulcerated. This feature, together with the histologic and cytologic features and apparent heteroploidy of the tumors, as revealed by their DNA content, indicated that the tumors were indeed neoplastic. Electron microscopic findings on the melanosomes in these melanomas at various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…He studied melanomas extensively in nibe croaker living in shallow sea waters in Japan [12]. As the pathology offish melanomas has been dealt with in detail elsewhere [2,5,[10][11][12][13][14] we will mention it only briefly here. Forty melanomas in five kinds of fish tumors were nielanotic, but a few were amelanotic.…”
Section: Smentioning
confidence: 99%
See 1 more Smart Citation
“…He studied melanomas extensively in nibe croaker living in shallow sea waters in Japan [12]. As the pathology offish melanomas has been dealt with in detail elsewhere [2,5,[10][11][12][13][14] we will mention it only briefly here. Forty melanomas in five kinds of fish tumors were nielanotic, but a few were amelanotic.…”
Section: Smentioning
confidence: 99%
“…Histologically, tumors were composed of dendritic or spindle-shaped tumorous melanocytes (Fig 5). The ultrastructure of fish melanoma has been described in detail [5,12,13]. Many melanosomes were densely aggregated in the main body of the cytoplasm and were also evident in the dendritic processes.…”
Section: Smentioning
confidence: 99%
“…The histopathological and genetic characteristics of melanomas induced by N-methyl-N-nitrosourea (MNU) or UV radiation help to classify various types of melanoma including (i) melanocytic melanomas, (ii) melanophorous- macromelanophorous polymorphic melanomas, (iii) spindle cell type melanomas, (iv) epithelioid cell melanomas and (v) amelanotic melanomas in vivo [86]. In the case of cross and backcross, both Xiphophorus maculatus and Xiphophorus helleri showed susceptibility to developing invasive melanoma by the radiation exposure and confirmed that fish can provide similar aspects to mammalian melanoma in vivo [91,92].…”
Section: Platyfish (Xiphophorus Sp)mentioning
confidence: 98%
“…These hybrid melanomas originate from cells within polymorphic pigment patterns derived from the platyfish strains, which become phenotypically enhanced in hybrid progeny, typically showing a large proportion of relatively undifferentiated, actively proliferating melanocytes (Anders, 1991; Gordon, 1959; Vielkind, 1976; Vielkind and Vielkind, 1982). Human melanomas also consist of melanocytes with poorly regulated proliferation (Sauter and Herlyn, 1998), and both Xiphophorus and human melanomas exhibit similarities in their histopathologies (Gimenez‐Conti et al., 2001; Grand et al., 1941; Ishikawa et al., 1975; Sobel et al., 1975; Vielkind and Vielkind, 1970; Vielkind et al., 1971). Transplanted Xiphophorus melanomas are vascularized and grow in nude mice in a manner indistinguishable from transplanted human melanomas, while maintaining expression of fish antigens (Schartl and Peter, 1988).…”
Section: Xiphophorus Melanoma Modelsmentioning
confidence: 99%